First, we need to determine the slope of the line using the given points.
The formula for slope, using two points (x1, y1) and (x2, y2), is:
slope = (y2 - y1) / (x2 - x1)
Using the given points (-6,4) and (3,2):
slope = (2 - 4) / (3 - (-6))
slope = (-2) / (3 + 6)
slope = (-2) / 9
Now that we have the slope, we can use it with one of the given points to form the equation in point-slope form. Let's use the point (-6,4):
y - y1 = m(x - x1)
where (x1, y1) is (-6,4), and m is the slope (-2/9).
Substituting these values into the equation:
y - 4 = (-2/9)(x - (-6))
Simplifying and putting the equation in point-slope form:
y - 4 = (-2/9)(x + 6)
Therefore, the equation in point-slope form for the given line is: y - 4 = (-2/9)(x + 6)
Write an equation in point-slop form for the give line.
(two points are (-6,4) and (3,2))
1 answer